Sulfurization of electrodeposited CuInSe2-based solar cells - Valdes, Matias Hernan (2010)
CuInSe2 (CISe) thin films have been prepared by single-step electrodeposition on top of TCO/TiO2 and TCO/TiO2/In2S3 coated electrodes. TiO2 and In2S3 have been deposited by spray–pyrolysis. The electrodeposition step is studied using cyclic voltammetry in an acidic electrolyte. Electrodeposited CISe is then subjected to two different thermal treatments. The first treatment is an annealing step under argon atmosphere, carried out to enhance the crystallinity of the film. The second consists of a sulfurization process, where sulfur is vaporized and mixed with the argon flux, leading to substantial changes in the composition of the chalcogenide. The crystallinity, morphology and stoichiometry of the annealed films are characterized by XRD, micro-Raman spectroscopy and SEM/EDX. Raman spectra and EDX show an almost complete replacement of the Se atoms by S atoms. Etching the films in KCN solution is a key step, enabling a final adjustment in the stoichiometry. The incorporation of In2S3 buffer layer in TiO2/CuIn(SeS)2 solar cells produces a marked improvement in the cell efficiency. Despite this improvement, the values of Jsc and the fill factor (FF) are relatively low, showing efficiencies below 1%, most likely associated to the resistances present in the multi-layered cell.